Economics of Wheat Production in Mohmand Agency, Khyber Pakhtunkhwa, Pakistan - Hina Gul; Sonia Sonia; Munir Khan; Khuram Nawaz Sadozai (Indonesian Journal of Agricultural Research, 2018)
The central theme of this research endeavour was to compute the cost and net returns of wheat crop. This study has also highlighted the significant variables contributing in wheat productivity. The study universe was two focused villages namely Malok-Korona and Peer-Qila of Ekaghund Tehsil, Mohmand Agency. The proportional allocation sampling technique was used to get the required sample size of 70 respondents. However, 26 respondents from Malok-Korona and 44 respondents from Peer-Qila were interviewed through face to face interview technique. The marked findings of this study divulge that vast majority of the farmers (61.43%) were using certified seed and the study area was predominantly dependent upon rainfall as reported by 60 % of the respondents. It is further revealed that the mean cost of production incurred by the sampled growers was estimated as Rs. 30,000 per acre. Income trend observed by 70 per cent of the respondent through wheat crop was found Rs.40000 per acre. The average income of farmers through wheat crop was Rs.35286 per acre. The estimated results of regression analysis corroborate the expected sign of the majority of coefficient of explanatory variables. Among explanatory variables seed, irrigation and labor days were significant while urea and FYM were found insignificant for crop yield. The study recommends that attempts for awareness, supply of loans, inputs like fertilizer, pesticide, apt agriculture approaches, demonstration plots and training programs should be made available to farmers for higher wheat production in Mohmand Agency.